An Analysis of Development Mechanism of China’s Smart Grid - Yuan, Xiaoling; Zhang, Jiangyang (International Journal of Energy Economics and Policy, 2014)
Through the perspectives of socio-technical systems, this paper summarizes characteristics of China’s smart grid and finds the influencing factors of development mechanism. We find that China’s smart grid featured by company-led, government striven to develop renewable energy, indigenous and multinational corporation both-driven, consumer-participated passively approach appears to differ from development pathways compared with other Western counties such as US, South Korea and Japan, then we assess strength and weakness of the development mechanism from three aspects including government, industrial and consumer. From a long run, China should establish flattening social innovation organization with government-led, stakeholders-participated jointly, then enact national blue planning, laws and technical standards, at last, develop ultra high voltage properly and actively promote development of distribution generation and micro grid. Keywords: Smart Grid; Development Mechanism; Government; Industrial; Consumer JEL Classifications: 030